"Regrets for leaving the 'zoo'?": Regret construction strategies in the online discourses of Nigerian migrants - Oluwafemi Jolaoso; Ezekiel Olajimbiti (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Regret, a cognitive phenomenon capable of revealing a person's disposition about certain realities, is conceived as a tool to unpack Nigerian migrants' perceptions about the country. This paper examines discourse strategies of regrets' construction in the online discourses of Nigerian migrants. The data consist of eighty-eight responses of Nigerian migrants downloaded from the NAIRALAND where many Nigerians in the diaspora expressed their regrets about leaving the country. These were subjected to qualitative-descriptive analysis, using van Dijk's (2007) model of discourse strategies. The findings uncover two forms of regrets constructed in the discourse: positive and negative. The positive regrets' construction characterizes "not leaving early" regrets; positive self-appraisal and negative representation of the country. Frustration experience in the foreign countries and juxtaposition of specific circumstances in Nigeria to contemporary experiences elsewhere frame negative regrets' construction. These were constructed through discourse strategies such as presupposition, implication, lexicalization, hyperbole, illustration, metaphor and disclaimer. These Nigerians' use of language in this discourse indexes hopelessness, visionless leaders, lawlessness and economic hardship. The study concludes that while the views of Nigerian migrants may not be true, perhaps, the government may urgently look into these views and act to convince other Nigerians to prevent the exodus of prospective Nigerian migrants which could lead to brain drain.